A "system dynamics perspective" of bioenergy governance and local, sustainable development. (20th November 2019) - Cavicchi, Bianca
Abstract: This study investigates the governance of bioenergy systems (BESs) and how it influences the bioenergy policy process and local sustainable development. The study compares the BES in Emilia Romagna and Hedmark. At first, bioenergy was expected to mitigate climate change and to tackle the crisis of the primary sectors and related industries. However, bioenergy policies were not equipped to address cross‐sectoral and multilevel issues. Therefore, they failed to secure the local, sustainable development. Critical weaknesses lie in BES governance. Actors' discourses, rules, and power issues form a complex structure that influences the bioenergy policy process and its outcomes. The study relies on systems thinking and system dynamics, and the pathways approach. It uses the system archetypes to investigate the bioenergy policy feedback dynamics and how to leverage local, sustainable development. Results show that power relations and social opposition are critical to a policy change that best secures local, sustainable development.